The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.adolescence.2017.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Within‐ and between‐person and group variance in behavior and beliefs in cross‐cultural longitudinal data☆

Abstract: a b s t r a c tThis study grapples with what it means to be part of a cultural group, from a statistical modeling perspective. The method we present compares within-and between-cultural group variability, in behaviors in families. We demonstrate the method using a crosscultural study of adolescent development and parenting, involving three biennial waves of longitudinal data from 1296 eight-year-olds and their parents (multiple cultures in nine countries). Family members completed surveys about parental negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 29 publications
5
30
0
Order By: Relevance
“…The Achenbach measures are among the most widely used instruments in international research, with translations in over 100 languages and strong, welldocumented psychometric properties (e.g., Achenbach and Rescorla 2001). This measure demonstrated adequate reliability across cultures at age 13 (Internalizing α = 0.89; Externalizing α = 0.87) and age 15 (Internalizing α = 0.73; Externalizing α = 0.75) and has demonstrated reliability and validity within all cultural groups in the present sample in past work (Lansford et al 2018a). Moreover, measurement invariance and consistency of the Youth Self Report factor structure has been demonstrated in numerous cultural groups worldwide, including those examined in the current study (e.g., Yarnell et al 2013).…”
Section: Adolescent Externalizing and Internalizing Behaviormentioning
confidence: 59%
See 2 more Smart Citations
“…The Achenbach measures are among the most widely used instruments in international research, with translations in over 100 languages and strong, welldocumented psychometric properties (e.g., Achenbach and Rescorla 2001). This measure demonstrated adequate reliability across cultures at age 13 (Internalizing α = 0.89; Externalizing α = 0.87) and age 15 (Internalizing α = 0.73; Externalizing α = 0.75) and has demonstrated reliability and validity within all cultural groups in the present sample in past work (Lansford et al 2018a). Moreover, measurement invariance and consistency of the Youth Self Report factor structure has been demonstrated in numerous cultural groups worldwide, including those examined in the current study (e.g., Yarnell et al 2013).…”
Section: Adolescent Externalizing and Internalizing Behaviormentioning
confidence: 59%
“…These findings indicate that the Chinese adolescents who were experiencing internalizing problems, and Swedish and Kenyan adolescents who were experiencing externalizing problems, disclosed less information to their parents over time. Another recent study (Lansford et al 2018a) found that China had the second-lowest overall levels of adolescent internalizing behaviors, and both Sweden and Kenya had some of the lowest overall levels of externalizing behaviors. It is possible that when adolescents in these cultures experience psychological problems that are especially rare, they may be even more disturbed or ashamed of such problems, and therefore even less likely to discuss such problems with their parents, compared to adolescents in other cultures where such problems are more normative.…”
Section: Are the Links Between Parent-adolescent Communication Effortmentioning
confidence: 97%
See 1 more Smart Citation
“…And, indeed, a great deal of research in this tradition has been cross-national. For example, the large-scale International Comparative Study of Ethnocultural Youth (Berry, Phinney, Sam & Vedder, 2006) compared acculturation strategies and adaptation across 13 countries and the Parenting Across Cultures Project examined processes associated with acculturation across 9 countries (Deater-Deckard et al, 2018). Despite the fact of these cross-national studies, there has been a dearth of contextualized cross-national studies of identity processes, studies that closely examine how identities develop within a particular cultural context.…”
Section: Immigrant Identities At the Intersection Of Self And Societymentioning
confidence: 99%
“…It is important to note that the E factor includes not only unique environmental factors but also measurement error. Recently, a longitudinal cross-cultural study investigating parenting and behavioral and emotional adjustment (based on self-reports) in children (8, 10, and 12 years old) showed that most variation was explained by within-person variability rather than between-person or between-group variability (Deater-Deckard et al, 2018). Accordingly, we believe that measurement error always plays a role when collecting data.…”
Section: Discussionmentioning
confidence: 90%